Pengaruh Pemberian Upah Dan Insentif Terhadap Produktivitas Kerja Pegawai Pada Kantor Badan Pertanahan Kota Bima: The Influence of Wages and Incentives on the Work Productivity of Employees at the Bima City National Land Agency Office - Meilan, Selfina; Mukhlis, Mukhlis; Aprianti, Kartin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to determine the effect of wages and incentives on employee work productivity at the Bima City Land Agency Office. The research instrument used a Likert scale questionnaire. The study population was 43 respondents with purposive sampling, a sample of 30 respondents was obtained. Data collection techniques were observation, questionnaires and literature studies. Analysis with multiple linear regression. The results of the study showed that partially wages did not have a significant effect on work productivity but incentives had a significant effect on work productivity. Simultaneously wages and incentives had a significant effect on work productivity.